Reflexive secularization? Concepts, processes and antagonisms of postsecularity. (August 2020) - Beaumont, Justin; Eder, Klaus; Mendieta, Eduardo
This article deals with the concepts, processes, and antagonisms that are associated with the notion of postsecularity. In light of this article's expanded interpretation of José Casanova on the secular and secularization, as well as thoughts on James A. Beckford's take on public religions, five rubrics on the postsecular derived from critical theory and an understanding of 'reflexive secularization' are presented. This term focuses on secularization processes and how these practices unleash complementary as well as antagonistic tendencies, a confrontation of normativities and specific social-empirical challenges. From this basis it is argued that social-empirical analysis should focus on non-naturalistic relations between individuals occupying structurally equivalent positions in narrative networks. A plurality of normativities are seriously considered as ideas circulating through social relations where the critical competence of the participants of such communication processes are provoked to subvert anything – including any normative positionality – as taken for granted. Moves towards the decolonization of the secular/postsecular dyad are emphasized, with ramifications for thinking about the urban, which point to the universal and authentic foundations of the human condition that are brought into play.